Letter from A. E. Outerbridge to James Curtis Booth - Outerbridge, Alexander E. (1864)
Alexander Outerbridge sends James Curtis Booth (1810-1888) a photograph of Echo Hall. Photograph is not included in the collection.
Keywords: Booth, James Curtis, 1810-1888